Knowledge discovery and knowledge validation in intensive care - Katharina Morik; Michael Imhoff; Peter Brockhausen; Thorsten Joachims; Ursula Gather (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
Operational protocols are a valuable means for quality control. However, developing operational protocols is a highly complex and costly task. We present an integrated approach involving both intelligent data analysis and knowledge acquisition from experts that supports the development of operational protocols. The aim is to ensure high quality standards for the protocol through empirical validation during the development, as well as lower development cost through the use of machine learning and statistical techniques. We demonstrate our approach of integrating expert knowledge with data driven techniques based on our effort to develop an operational protocol for the hemodynamic system.
Keywords: 519; operational protocols; online-monitoring; time series analysis; machine learning; statistical pattern recognition; knowledge based systems; knowledge validat